2011
DOI: 10.5209/rev_sjop.2011.v14.n2.12
|View full text |Cite
|
Sign up to set email alerts
|

Father Involvement and Marital Relationship during Transition to Parenthood: Differences between Dual and Single-Earner Families

Abstract: Research into the process of becoming mother or father shows very conclusively that this important life transition is accompanied by both a decrease in marital quality and a more traditional division of labour. In this paper these changes are analyzed with special emphasis on the relationships between them and exploring the role played in this process by the mother's work status. Results showed a significant link between the development of marital quality and violated expectations regarding father involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
5
0
4
Order By: Relevance
“…In line with previous research by Menendez, Hidalgo, Jimenez & Moreno (2011) showed a positive relationship in a longitudinal study of parenting processes in 79 couples and 29 mothers. In this study there were two research sessions, where the first session was in the first trimester of pregnancy of the mothers (T1) and at the age of one year (T2).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous research by Menendez, Hidalgo, Jimenez & Moreno (2011) showed a positive relationship in a longitudinal study of parenting processes in 79 couples and 29 mothers. In this study there were two research sessions, where the first session was in the first trimester of pregnancy of the mothers (T1) and at the age of one year (T2).…”
Section: Discussionsupporting
confidence: 92%
“…Os cuidados ao bebê são bem diferentes dos esperados antes do nascimento, ainda mais quando as expectativas são violadas. Além disso, a adaptação à paternidade implica muitas vezes em maior compromisso com o relacionamento como pais e menor como cônjuges (15) . Em contraponto a esses sentimentos negativos, alguns pais referiram a primeira noite como tranquila e até mesmo como esperada, já que o sentimento maior era de ter o filh em casa.…”
Section: Discussionunclassified
“…A própria internação muitas vezes prolongada, gera nesses pais ansiedade para a alta hospitalar e chegada do filho no domicílio, e quando isso ocorre surgem sentimentos de alegria e satisfação (16) . Os pais com expectativas boas antes do nascimento em relação ao filh , após o nascimento participam de forma mais Zani efetiva, com satisfação conjugal e menor desgaste nessa fase de transição (15) . As contrastantes experiências positivas e negativas podem estar relacionadas com as fases do novo papel parental, sendo a maioria das respostas emocionais durante a gravidez e até dois anos após o nascimento mais negativas do que positivas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por ejemplo, es más perjudicial para el ajuste adolescente que las madres muestren un estilo indiferente a que lo hagan los padres (Simons y Conger, 2007), quizá porque para el bienestar adolescente son centrales el afecto materno (Cheng y Furnham, 2004), la comunicación con la madre (Morrow, 2004) y la calidad de la relación con la madre (Trzcinski y Holst, 2008). Tampoco hay que olvidar en esta consideración que la mayor dedicación e influencia de la madre frente al padre responde mejor a las expectativas que nuestra cultura tiene puestas en ambos (Menéndez y Hidalgo, 2003;Menéndez, Hidalgo, Jiménez y Moreno, 2011).…”
Section: Discussionunclassified